Renin-Angiotensin-System Inhibitors Are Associated With Lower In-hospital Mortality in COVID-19 Patients Aged 80 and Older - Spannella, Francesco; Giulietti, Federico; Di Pentima, Chiara; Allevi, Massimiliano; Bordoni, Valentina; Filipponi, Andrea; Falzetti, Sara; Garbuglia, Caterina; Scorcella, Samuele; Giordano, Piero; Sarzani, Riccardo (Frontiers in Cardiovascular Medicine, 2022)
Background: Older adults are at higher risk of morbidity and mortality for COVID-19. Renin angiotensin-system-inhibitors (RASi) were found to have neutral or protective effect against mortality in COVID-19 adult patients. Aims: We investigated whether this association was confirmed also in COVID-19 older patients. Methods: Prospective observational study on 337 hospitalized older adults (aged 80 years and older). We classified the study population according to RASi use before and during hospitalization. A propensity score analysis was also performed to confirm the findings. Results: Mean age was 87.4±6.1 years. Patients taking RASi at home were 147 (43.6%). During hospitalization, 38 patients (11.3% of the entire study population) discontinued RASi, while 57 patients (16.9% of the entire study population) started RASi. In-hospital mortality was 43.9%. Patients taking RASi during hospitalization (patients who maintained their home RASi therapy + patients who started RASi during hospitalization) had a significant lower in-hospital mortality than untreated patients [HR 0.48 (95% CI 0.34 - 0.67)], even after adjustment for required respiratory support, functional status, albumin, inflammation and cardiac biomarkers. The analysis on the groups derived from the ‘propensity score matching’ (58 patients in each group) confirmed these results [HR 0.46 (95% CI 0.23 - 0.91)]. Discussion: Despite the high risk of death in older COVID-19 patients, RASi therapy during hospitalization was associated with clinically relevant lower in-hospital mortality, likely due to the benefit of RAS modulation on cardiopulmonary system during the acute phase of the disease. Conclusions: Our findings confirm the protective role of RASi even in COVID-19 patients aged 80 years and older.